Transformasi Industri 4.0: Mengubah Lanskap Manufaktur dan Ekonomi Global - SUTIONO, DANI SUTIONO (Maliki Interdisciplinary Journal, 2025)
The Fourth Mechanical Transformation brings noteworthy changes to the fabricating division and the worldwide economy. By coordination progressed advances such as manufactured insights, the Web of Things (IoT), and information analytics, this change leads to higher productivity, adaptability, and efficiency. This article looks at the affect of these advances on conventional fabricating forms and their broader impacts on the worldwide financial structure, counting shifts in labor designs and universal exchange. The ponder moreover investigates usage challenges over diverse nations. This change makes openings whereas posturing dangers that got to be deliberately overseen to guarantee financial maintainability. These rules should include strict data security standards, privacy protection mechanisms, and incentives for research and development in security technologies.